2019
DOI: 10.1051/0004-6361/201936004
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation of a small-scale cometary plasma environment

Abstract: Context. The plasma near the nucleus of a comet is subjected to an electric field to which a few different sources contribute: the convective electric field of the solar wind, the ambipolar electric field due to higher electron than ion speeds, and a polarisation field arising from the vastly different ion and electron trajectories. Aims. Our aim is to show how the ambipolar and polarisation electric fields arise and develop under the influence of space charge effects, and in doing so we paint a qualitative pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…By computing the Doppler shift and comparing observed spectra with wave theory and known properties of current-driven ion acoustic waves we can estimate the angle between the bulk velocity of the cold ions and the propagation direction of the waves to be α 50 • for closest approach and α 70 • farther out when Rosetta was moving away and the wave power decreasing. Previous estimates have shown that ions move away from the centre of the comet, predominantly in a radial direction (Odelstad et al, 2018) as would be expected if they are accelerated by the ambipolar field present in the inner coma (Gunell et al, 2019). There are also observations of ions with an anti-sunward velocity component (Berčič et al, 2018), but those ions were faster than the (3-3.7) km s −1 we have observed here.…”
Section: Discussionsupporting
confidence: 72%
“…By computing the Doppler shift and comparing observed spectra with wave theory and known properties of current-driven ion acoustic waves we can estimate the angle between the bulk velocity of the cold ions and the propagation direction of the waves to be α 50 • for closest approach and α 70 • farther out when Rosetta was moving away and the wave power decreasing. Previous estimates have shown that ions move away from the centre of the comet, predominantly in a radial direction (Odelstad et al, 2018) as would be expected if they are accelerated by the ambipolar field present in the inner coma (Gunell et al, 2019). There are also observations of ions with an anti-sunward velocity component (Berčič et al, 2018), but those ions were faster than the (3-3.7) km s −1 we have observed here.…”
Section: Discussionsupporting
confidence: 72%
“…Bow shocks have been studied at comets and elsewhere in the solar system (see e.g. Martinecz et al, 2008;Fahr and Siewert, 2015;Hall et al, 2016), but so far the development of a bow shock could not be observed, simply because a bow shock had already been fully formed. Comets provide an excellent laboratory to investigate the process of bow shock formation, where the gradual increase in gas production rate over weeks or months means that the intermediate stages of this interaction can be observed and studied.…”
mentioning
confidence: 99%
“…The Rosetta data sets are available in the ESA Planetary Science Archive at https://archives.esac.esa.int/ psa (last access: 21 December 2020, European Space Agency, 2020). The specific data set used in this article is available at https://doi.org/10.5281/zenodo.3973232 (last access: November 2020), together with computer codes to produce the figures (Gunell et al, 2020).…”
Section: Appendix A: Dispersion Relationsmentioning
confidence: 99%
“…were named "singing comet" waves; they have been interpreted in terms of a modified ion-Weibel instability (Meier et al, 2016), found to be compressional (Breuillard et al, 2019) and detected as far as 800 km from the nucleus (Goetz et al, 2020). Waves in the lower hybrid frequency range (f 15 Hz) were found by André et al (2017) and Karlsson et al (2017).…”
Section: Introductionmentioning
confidence: 99%